Implementasi Desain Jaringan Hotspot Berbasis Mikrotik dengan Metode Network Development Life Cycle (NDLC) Pada PT Kirana Permata - Muhamad Malik Fajar (Institute of Information Technology and Social Science (IITSS), 2021)
The development of information technology has made the internet a primary necessity for supporting company operational activities. PT Kirana Permata, as a rubber processing company, requires a stable and well-managed internet network to support employee and guest activities. However, the uneven distribution of hotspot networks and the lack of security and bandwidth management have resulted in suboptimal network utilization. This study aims to design and implement a Mikrotik-based hotspot network using the Network Development Life Cycle (NDLC) method to improve the efficiency of computer network usage at PT Kirana Permata. The NDLC method includes the stages of analysis, design, simulation, implementation, monitoring, and management. The results show that the new network topology successfully expanded hotspot coverage to all employee dormitory areas. The implementation of bandwidth management produced balanced speed limitations, with an average download speed of 2.55 Mbps and an upload speed of 2.01 Mbps. In addition, the implementation of a login system improved network security. Thus, the implementation of a Mikrotik-based hotspot network using the NDLC method proved effective in enhancing the quality, security, and equity of internet access within the PT Kirana Permata environment.